Peluang Meningkatkan Pendapatan Duty Free Shop - Pintanugra P. Tarigan; Cut Nyak Shahnaz Rakadiny; Alit Sodikin (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
PT. Angkasa Pura II is a company that manages airport services and air traffic services that prioritizes flight safety and customer satisfaction, in an effort to provide optimal benefits to shareholders, business partners, employees, the community and the environment by upholding business ethics. The author used data from field through interviews, observations, and questionnaires to analyze the problem. Based on the IE matrix, the company's position is in cell II, which is in the position of growing and developing, with a total score of internal factors 2.78 and external factors 3.05 so that alternative strategies that can be carried out are market penetration, market development and product development and (Backward Integration, Forward Integration, Horizontal Integration). While in the SWOT analysis using IFE and EFE tables, the internal strength factor is 3.70 and the weakness factor is 3.35, so the difference between the two factors is 0.35. Moreover, the external opportunity is 3.60 and the threat factor is 3.40, so the difference between the two external factors is 0.2. The conclusion of the research based on the SWOT diagram is that the company's position is in quadrant I, where the company has great strengths and opportunities, so that in the SWOT matrix the company's position is in the S-O strategy.